2011
DOI: 10.1007/s00455-011-9376-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics of Dysphagia Following Thermal Burn Injury

Abstract: 1 This project was supported by funding from the Royal Brisbane and Women's Hospital (RBWH) Foundation. 2 Physiological characteristics of dysphagia following thermal burn injury 3 AbstractThe study aim was to document the acute physiological characteristics of the swallowing impairment following thermal burn injury. A series of 19 participants admitted to a specialised burn centre with thermal burn injury were identified with suspected aspiration risk by a clinical swallow examination (CSE) conducted by a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
(52 reference statements)
1
10
0
3
Order By: Relevance
“…Reduced pharyngeal and laryngeal sensation has been found to be a common feature in the thermal burns population with prior research reporting that 77% of cases in a cohort study had minimal or no response to contact of the scope to the hyopharyngeal structures during FEES (Rumbach et al, 2012b). Silent aspiration, as evidenced by the cases presented here, may be a possible outcome (Rumbach et al, 2009b;Rumbach et al, 2012b). The ability to use repeated FEES assessments to follow changes to swallowing physiology over the recovery period revealed that these sensory deficits improved greatly over the two-week period between the initial and repeat FEES in both cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduced pharyngeal and laryngeal sensation has been found to be a common feature in the thermal burns population with prior research reporting that 77% of cases in a cohort study had minimal or no response to contact of the scope to the hyopharyngeal structures during FEES (Rumbach et al, 2012b). Silent aspiration, as evidenced by the cases presented here, may be a possible outcome (Rumbach et al, 2009b;Rumbach et al, 2012b). The ability to use repeated FEES assessments to follow changes to swallowing physiology over the recovery period revealed that these sensory deficits improved greatly over the two-week period between the initial and repeat FEES in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Rumbach and colleagues (2012b) reported on 13 patients with dysphagia after thermal burn injury using fiberoptic endoscopic evaluation of swallowing (FEES) conducted at an average of one month (range = 5-80 days) post injury. FEES assessment confirmed numerous pharyngeal phase deficits, with impaired secretion management, laryngotracheal oedema, delayed swallow initiation, impaired sensation, inadequate movement of hypophyaryngeal and laryngeal structures, and the presence of diffuse pharyngeal residue being evident in greater than 50% of the cohort (Rumbach et al, 2012b). Penetration and aspiration was also found to be prevalent (83% of thin fluid trials), with penetration/aspiration being silent in 50% of cases (Rumbach et al, 2012b).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations